2018
DOI: 10.3233/nre-172412
|View full text |Cite
|
Sign up to set email alerts
|

Been there, done that, so what’s next for arm and hand rehabilitation in stroke?

Abstract: The good news is that there is evidence that we learned from the past and have invented a future that appears to be much more exciting and promising than the past.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 104 publications
1
37
0
2
Order By: Relevance
“…Numerous studies have shown that rehabilitation interventions are beneficial across a number of neurological conditions as they result in a decrease in the severity of disability 8 , 9 . However, choosing the most effective intervention among the myriad of available rehabilitation approaches is challenging 10 12 . High variability in response to interventions aimed to restore upper-limb function is observed across patients 13 15 , hence pointing to the need for designing “precision rehabilitation” interventions that account for the unique characteristics of each individual.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that rehabilitation interventions are beneficial across a number of neurological conditions as they result in a decrease in the severity of disability 8 , 9 . However, choosing the most effective intervention among the myriad of available rehabilitation approaches is challenging 10 12 . High variability in response to interventions aimed to restore upper-limb function is observed across patients 13 15 , hence pointing to the need for designing “precision rehabilitation” interventions that account for the unique characteristics of each individual.…”
Section: Introductionmentioning
confidence: 99%
“…To support their use, researchers and developers often emphasize the potential advantages of VR/AVG systems over conventional interventions, including that these technologies may enhance a patient’s affective experience in therapy for the purpose of facilitating recovery [8–11]. Examining the role of affective factors for motor learning is an emerging area of emphasis in rehabilitation [2, 1215].…”
Section: Introductionmentioning
confidence: 99%
“…That a measure of attention/arousal predicted non-use behavior above and beyond sensorymotor functioning highlights the importance of motivated engagement to drive use of the paretic limb. As such, it is increasingly clear that rehabilitation efforts are more likely to be successful when they engage the participant by providing meaningful task practice and motivational enhancements (see 55 for discussion). Larger-scale studies of the nonuse phenomenon in individuals ranging in severity, and with incorporation of additional measures (e.g., mental health, lesion volume and white matter connectivity, pain, traitand state-level motivation) will be required to extend these findings.…”
Section: Resultsmentioning
confidence: 99%